Estetika Pertunjukan Wayang Kulit Lakon Tripama Kawedhar Sajian Cahyo Kuntadi - Ari Nurzeto; Bagong Pujiono (Lakon Jurnal Pengkajian & Penciptaan Wayang, 2019)
The research entitled " Estetika Pertunjukan Wayang Kulit Lakon Tripama Kawedhar Sajian Cahyo Kuntadi" aims to reveal the aesthetic elements and their implementation in wayang kulit performance Lakon Tripama Kawedhar presented by Cahyo Kuntadi. This problem is studied using the aesthetic thought by Sunardi and Najawirangka. The analysis of this research is descriptive qualitative using data collection techniques through the literature study, observation, and interviews. The results show that, firstly, the aesthetic elements of the wayang performance, Tripama Kawedhar, can be observed through lakon, sabet, catur, and karawitan pakeliran. Secondly, the achievement of the aesthetic concept of puppetry is manifested through the success of the puppeteer in building an atmosphere of impressive scene of feeling regu , greget, nges, sem, renggep, antawacana, lucu, unggah-ungguh, tutuk and trampil. Cahyo Kuntadi succeeded in performing Lakon Tripama Kawedhar aesthetically.